Immunotherapy against tau fragment diminishes AD pathology, improving synaptic function and cognition - Jie Xiang; Zhengjiang Qian; Ye Xi; Yanuo Wei; Guangxing Wang; Xia Liu; Zhi-Hao Wang; Zhentao Zhang; Shengxi Wu; Keqiang Ye (Molecular Neurodegeneration)
Abstract Background Asparagine endopeptidase (AEP) is implicated in the pathogenesis of Alzheimer’s disease (AD) by cleaving Tau at residue N368, accelerating its hyperphosphorylation and aggregation. The Tau N368/t-Tau ratio in cerebrospinal fluid (CSF) serves as a superior biomarker compared to established biomarkers (p-Tau 181/217) for correlating with tau pathology and synaptic dysfunction in patients with AD, highlighting its diagnostic and therapeutic potential. Methods We evaluated the therapeutic efficacy of a Tau N368-specific antibody in two mouse models: Tau P301S (tauopathy) and 3xTg (AD with Aβ/tau pathology). We conducted chronic intraperitoneal administration of the antibody to evaluate its effects on tau aggregation, synaptic integrity, and cognitive function. Neuropathological changes, synaptic plasticity (through electrophysiology), and behavioral outcomes were analyzed alongside Aβ pathology and neuroinflammation in 3xTg mice. Results Treatment with the anti-Tau N368 antibody significantly diminished neurofibrillary tangles (NFTs) formed of hyperphosphorylated/truncated Tau in both models. Clearance of Tau restored BDNF/TrkB neurotrophic signaling, improved synaptic plasticity, and alleviated cognitive deficits. In 3xTg mice, this treatment also reduced Aβ deposition and neuroinflammation, resulting in enhanced learning and memory. Notably, the antibody’s effectiveness in alleviating both tau and Aβ pathologies indicates a potential interaction between these pathways. Conclusions Targeting Tau N368 through immunotherapy alleviates tau-driven neurodegeneration, restores synaptic function, and improves accompanying Aβ pathology in AD models. Our results confirmed that Tau N368 is an exceptional biomarker and a promising therapeutic target, disrupting AD progression by addressing tau aggregation and its downstream effects.